2021
DOI: 10.1097/corr.0000000000002006
|View full text |Cite
|
Sign up to set email alerts
|

Unhelpful Thoughts and Distress Regarding Symptoms Limit Accommodation of Musculoskeletal Pain

Abstract: BackgroundAmong people with musculoskeletal disorders, much of the variation in magnitude of incapability and pain intensity is accounted for by mental and social health opportunities rather than severity of pathology. Current questionnaires seem to combine distinct aspects of mental health such as unhelpful thoughts and distress regarding symptoms, and they can be long and burdensome. To identify personalized health strategies, it would be helpful to measure unhelpful thoughts and distress regarding symptoms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 19 publications
0
58
0
Order By: Relevance
“…The realization that pain is due to a gradual onset condition that is age-appropriate can be counterintuitive. A strong therapeutic relationship—one that includes trust, common understanding, and engagement—can help patients develop healthy thoughts (e.g., “Even though this hurts, I can get through it”), an adaptive mindset, and a supportive environment—all of which can limit symptom intensity and activity intolerance as one ages ( 12 , 20 , 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…The realization that pain is due to a gradual onset condition that is age-appropriate can be counterintuitive. A strong therapeutic relationship—one that includes trust, common understanding, and engagement—can help patients develop healthy thoughts (e.g., “Even though this hurts, I can get through it”), an adaptive mindset, and a supportive environment—all of which can limit symptom intensity and activity intolerance as one ages ( 12 , 20 , 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on this, we performed a factor analysis and identified 2 separate factors—one regarding thoughts and the other regarding feelings—addressed by these questionnaires, although the 2 factors were highly related. 24 We found that we could use just a few questions to capture distress regarding symptoms in a way that people are more likely to answer forthrightly. These items include statements such as “I feel I can't stand it anymore,” “I keep thinking about how much it hurts,” and “It's awful, and it overwhelms me.” I think we can get to just a few items, each of which feels relevant, and each serving as a point of discussion.…”
Section: Diagnosis Of Opportunities For Improved Mental and Social He...mentioning
confidence: 99%
“…The important line of research started by Teunis et al [10] should continue. Future studies should investigate the best approaches to help people with psychosocial challenges and musculoskeletal symptomatology and the efficacy of integrated multidisciplinary teams [1, 4, 5].…”
Section: How Do We Get There?mentioning
confidence: 99%
“…The authors [10] may be bringing us ever closer to identifying personal characteristics (phenotypes) and red-flag statements that can help us identify the underlying stresses that may affect a person's recovery. Still, we need to refine these questionnaires, reduce the number of questions needed to get the answers we want, and identify common phrases utilized by our patients that point to psychosocial challenges that may affect patient recovery.…”
mentioning
confidence: 99%
See 1 more Smart Citation